Oregano and thyme by-products of olive oil aromatization process with microwave assisted extraction as a rich source of bio-active constituents - Dina, Evanthia; Cheilari, Antigoni; Vontzalidou, Argyro; Karamani, Dimitra; Diamanti, Ioanna; Bagatzounis, Panagiotis; Giannenas, Ilias; Grigoriadou, Katerina; Aligiannis, Nektarios (Frontiers in Nutrition, 2024)
Introduction Processing of Medicinal Aromatic Plants (MAPs) results in the production of a significant amount of by-products, which are not commercially exploitable. Towards this direction, we studied extensively the by-products of oregano and thyme, remaining after the aromatization of olive oils with microwave assisted extraction (MAE). The purpose of the study was the exploitation of the “wastes” of these two economically significant herbs of Greece, for the potential development of innovative bioactive products. Methods Hence, superior and inferior quality plant material from Origanum vulgare subsp. hirtum and Thymus vulgaris, were extracted with extra virgin olive oil using MAE. For the evaluation of raw plant material, beside the characterization of the essential oils (EOs), the hydroalcoholic extracts of superior and inferior plant material were afforded by ultrasound assistant extraction (UAE). In addition, the remaining plant material after the flavoring of olive oil by MAE, was extracted with c-Hex, MeOH, H2O:MeOH using UAE. All the extracts were evaluated for their DPPH free radical scavenging activity and total phenolic content (TPC) as well as their chemical profile was investigated by HPTLC. In parallel, the EOs, the olive oils and the c-Hex extracts were analyzed by GC–MS and Headspace Solid Phase Microextraction (HS-SPME)-GC–MS. Results and Discussion The results showed that the composition of the EOs and the volatile fraction of the olive oil extracts were similar for the superior quality material whereas for the inferior the composition of the volatile fraction of olive oil extracts was not analogous to the respective EOs. GC–MS analyses of oregano and thyme by-products revealed the presence of carvacrol, thymol, γ-terpinene and p-cymene among the major constituents. Moreover, the hydroalcoholic extracts obtained from the plant material remaining after olive oil flavoring with MAE showed similar phenolic content and scavenging activity with the hydroalcoholic extracts of the corresponding raw plant materials underlying their potent use in the preparation of high-added value products such as nutraceuticals and cosmeceuticals as well as enriched animal nutrition products.